BIOSORPTION CHARACTERISTICS OF SUGARCANE BAGASSE FOR THE REMOVAL OF FORON BLUE E-BL DYE FROM AQUEOUS SOLUTIONS - S. Zaheer; H. N. Bhatti; S. Sadaf; Y. Safa; M. Zia-ur-Rehman (Journal of Animal and Plant Sciences, 2014)
This study presents the biosorption characteristics of sugarcane bagasse for the removal of Foron Blue E-BL (FB), a disperse dye, from aqueous solutions in a batch system. Effect of different parameters i.e., pH, biosorbent dose, contact time, initial dye concentration and temperature was studied. Effect of surfactants, salt, and heavy metal ions was also investigated. Maximum biosorption capacity of native sugarcane bagasse was found to be at pH 4 whilein pretreated and immobilized forms, the biosorbent depicted maximum dye removal at pH 7 with 0.05g biosorbent dose at 30 °C temperature. An equilibrium time of 120 min was observed for maximum removal of the dye with native and pretreated sugarcane bagasse while immobilized sugarcane bagasse required only 90 min to establish saturation point. The saturation point was obtained with 100 mg/L dye concentration. Salt caused an increase in the biosorption capacity, while heavy metal ions and surfactants decreased the biosorption capacity of the biosorbent. Kinetics of biosorption followed the pseudo 2nd order mechanism. Thermodynamics of dye biosorption showed the exothermic nature of process. The results showed that sugarcane bagasse could be used as a promising biomass for the removal of FB from aqueous solutions.
Keywords: Biosorption; Disperse dyes; Sugarcane bagasse; Immobilization; Modeling